Medium tumor antigen of polyomavirus transformation-defective mutant NG59 is associated with 73-kilodalton heat shock protein. - Walter, G (1987)
Affinity-purified medium T antigen encoded by NG59, a nontransforming mutant of polyomavirus, is specifically associated with a protein of 72,000 daltons (72K protein). Medium T antigens of wild-type polyomavirus and the transformation-competent mutant dl8 are not associated with the 72K protein. Instead, they form a complex with another protein of 61,000 daltons. Several lines of evidence suggest that the medium T antigen-associated 72K protein is equivalent to the abundant and constitutive 73K heat shock protein. First, on two-dimensional polyacrylamide gels the 72K protein migrated with the same pI (5.6) as did the 73K heat shock protein. Second, the 72K protein was immunoprecipitable with antibodies against heat shock proteins. Third, when digested with V8 protease, the 72K protein gave rise to the same pattern of fragments as did the 73K heat shock protein.